Study on the Critical Dynamics of Compound Erosion in the Pisha Sandstone Area. Issue 1 (June 2020) - Yang, Chunxia; Zhen, Bin; Xiao, Peiqing; Zhang, Pan
Abstract: The Pisha sandstone area which was distributed in Ordos of Inner Mongolia was the main source area of Yellow River sediment. The area has a characteristic of serious composite erosion and fragile ecological environment. So it is an important prerequisite to identify the critical force occurrence conditions of compound erosion for prevent and control the multiple composite erosion. Using the method such as field observation, simulation experiments and literature review, this study preliminarily summarizes the dynamic critical conditions and key influencing factors of water erosion, wind erosion and freeze-thaw erosion.